Pengaruh Literasi Keuangan, Perilaku Hedonisme, Dan Tingkat Pendidikan Terhadap Pengelolaan Keuangan Pribadi (Studi Kasus Perusahaan Tekstil di Kota Bandung) - Ayub Girson Batee; Diah Febriyanti; Salza Adzri Arismutia (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study is designed to empirically examine how financial literacy, hedonistic behavioral tendencies, and formal educational background contribute to the quality of personal financial management, particularly among textile industry workers in Bandung City. The research adopts a quantitative-descriptive design using a questionnaire-based survey instrument distributed to 150 respondents selected through purposive sampling. Measurement instruments were constructed using a Likert scale (1-5) format and analyzed via multiple linear regression. Core findings reveal that: (1) financial literacy competency exerts a positive and statistically significant impact on personal financial management (β = 0.412; p < 0.01); (2) hedonistic lifestyle orientation significantly diminishes financial management capacity (β = −0.284; p < 0.01); (3) formal education level makes a positive and significant contribution (β = 0.198; p < 0.01); and (4) all three predictor variables jointly account for 53.4% of the variance in personal financial management (R² = 0.534). The implications of this study underscore the critical importance of strengthening systematic, industry context-based financial education programs.